Characterisation of buffalo (bubalus bubalis) bone gelatin extracted using acid and papain pre-treatment - Muhammad Yazid Samatra (2023)
Gelatin is a versatile biopolymer with numerous industrial uses, but traditional sources like bovine and porcine raise safety and religious concerns. Alternatives like fish gelatin often require further refining for quality enhancement. Buffalo bone gelatin offers a promising solution as it is free from diseases and religious restrictions. The extraction process, however, requires a thorough understanding of the complex bone structure to recover collagen for gelatin production. The extraction of gelatin from buffalo bone has yet to be extensively explored and holds great potential. This study explored the effects of pre-treatment conditions using different acids and concentrations, with and without papain, on the properties and extractability of gelatin derived from buffalo bone. The buffalo bone was pre-treated with hydrochloric acid (HCl) and citric acid at 0.05 M and 0.025 M concentrations, respectively, with and without papain (100 U/g), prior to hot water extraction. The study compared the physicochemical and functional properties of buffalo bone gelatin with standard bovine gelatin (SBG). The highest yield (6.36 %, dry weight) and hydroxyproline content (26.98 g/100g) was obtained from gelatin extracted using 0.025 M HCl pre-treatment without papain. Pre-treatment with 0.05 M citric acid without papain resulted in the lowest yield (3.79 %, dry weight) with hydroxyproline content of 12.49 g/100g. Papain significantly influenced the yield of gelatin in citric acid but not in HCl treatment when used at 100 U/g. Buffalo bone gelatin had significantly (p<0.05) lower moisture content than SBG and had a pH range of 5.11 to 5.44, indicating it is Type A gelatin. The gelatin was whiter with HCl pre-treatment and slightly yellow with citric acid pre-treatment. Low ash content (<2%) confirmed effective removal of minerals. Gelatin treated with 0.025 M citric acid without papain had the highest emulsion activity index (9.52 m2/g), emulsion stability index (30.29 min), foaming expansion (13.66 %), foaming stability (10.64 to 12.46 min), water holding capacity (11.68 mL/g), and fat binding capacity (8.88 mL/g). The Fourier Transform Infrared Spectroscopy (FTIR) results of all gelatin shown a similar secondary structure to SBG with the presence of Amide A, B, I, II and III. Papain used in HCl and citric acid pre-treatment resulted in degradation of α and ß components, which produced the lowest gel strength (20.35 g by 0.05 M citric acid with papain). The highest gel strength (50.64 g) was produced from 0.025 M citric acid without papain treatment. Buffalo bone gelatin shows potential as an alternative source of halal gelatin manufacturing.